The New Pregnancy and Lactation Labeling Rule - Pernia, Sonia (P T, 2016)
To address the need for updated pregnancy risk categories, the Food and Drug Administration published a final rule in 2014. The authors review the changes the rule makes, its implementation schedule, and its potential clinical impact.